Implementation of Class Policy Based on the Reception of Vocational High School Teachers - Sukma, Dimas Pramata; Supriyanto, Teguh; Mardikantoro, Hari Bakti; Pristiwati, Rahayu (Journal La Edusci, 2025)
The role of teachers in shaping students’ character and ideology in Vocational High Schools (SMK) is essential, particularly in internalizing the values of heroism courage, sacrifice, integrity, and dedication. This study explores how gender differences among teachers influence classroom policy implementation as a medium for instilling the ideology of heroism. Using a qualitative descriptive approach and Moser’s research design (1989), the study analyzes how 50 SMK teachers (25 male and 25 female) in Tegal Regency respond to heroic values after reading Eko Prasetyo’s novel "Poor People Are Forbidden from Going to School." Data were collected through instruments reflecting teachers' classroom policies and analyzed based on gender differences. Results show that female teachers generally implement classroom policies with greater tolerance, such as permitting students to leave class for competitions or excusing those who accompany peers in the school clinic. In contrast, male teachers are more likely to adhere to strict rule enforcement, such as reprimanding students who fall asleep despite working for their families. However, both male and female teachers avoided imposing severe punishments, demonstrating a shared understanding of the educational context. This study confirms that while the core values of heroism are shared, gender influences the methods of ideological internalization. These findings contribute to understanding pedagogical gender dynamics and emphasize the need for a standardized and consistent approach to character education to avoid value confusion among students.